Implementasi Strategi Ekspositori Dalam Pembelajaran Pendidikan Agama Islam Di SMK N 1 Payakumbuh - Mutia Joni Putri; Wedra Aprison; Iswantir Iswantir; Afrinaldi Afrinaldi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This research is based on the implementation of the expository strategy by the teacher in the monotonous learning of telling stories so that it was found that students ignore the teacher's explanation and are busy in the background. Students make noise in the class and don't listen to the teacher's explanation. This type of research is qualitative research with a descriptive approach. Data collection in this research was obtained by the author through interviews and observations. The data source for this writing was obtained from PAI teachers as key informants and students as supporting informants. Data analysis technique is done with data reduction, data presentation, and conclusion. Then data validity technique using source triangulation. From the results of the researcher's findings, it can be understood that the teacher has implemented an expository strategy with preparatory steps starting with opening the lesson with greetings, praying and reading the Al-Qur'an together, doing literacy activities and creating light conversations to increase students' enthusiasm in learning. Presentation step by explaining the material with a verbal approach. Correlation step by providing examples that are easy for students to find or with experiences that students have gone through. Application step by giving training tasks to students related to the material. The step concludes by summarizing the learning with the students at the end of the learning, but not making a conclusion with a mind map that is easy for the students to understand. While the obstacles that occur are in the form of internal obstacles that come from the teacher himself, and external obstacles that come from students, from the media used, and from the surrounding environment.